2012
DOI: 10.1021/bm300472y
|View full text |Cite
|
Sign up to set email alerts
|

Elastin-Like Peptide Amphiphiles Form Nanofibers with Tunable Length

Abstract: Peptide amphiphiles (PAs) self-assemble nanostructures with potential applications in drug delivery and tissue engineering. Some PAs share environmentally responsive behavior with their peptide components. Here we report a new type of PAs biologically inspired from human tropoelastin. Above a lower critical solution temperature (LCST), elastin-like polypeptides (ELPs) undergo a reversible inverse phase transition. Similar to other PAs, elastin-like PAs (ELPAs) assemble micelles with fiber-like nanostructures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 37 publications
0
54
0
Order By: Relevance
“…Second, the morphologies of ELPs exploited for drug delivery will realize a growing diversity as we obtain a greater understanding of the parameters that can drive ELP self-assembly. Structures such as vesicles [120], nanofibers [121], and nanoworms [122] have already been observed with vehicle systems containing an ELP component. Advances in the de novo design of such morphologies by experimental determination—or alternatively, theoretical prediction—of the phase diagrams of these systems is critical because it will allow the a priori design, at the amino acid sequence level, of drug carriers with tunable sizes and morphologies.…”
Section: Conclusion Future Directions and Challengesmentioning
confidence: 99%
“…Second, the morphologies of ELPs exploited for drug delivery will realize a growing diversity as we obtain a greater understanding of the parameters that can drive ELP self-assembly. Structures such as vesicles [120], nanofibers [121], and nanoworms [122] have already been observed with vehicle systems containing an ELP component. Advances in the de novo design of such morphologies by experimental determination—or alternatively, theoretical prediction—of the phase diagrams of these systems is critical because it will allow the a priori design, at the amino acid sequence level, of drug carriers with tunable sizes and morphologies.…”
Section: Conclusion Future Directions and Challengesmentioning
confidence: 99%
“…In the same vein, others have exploited the conjugation of hydrophobic groups to ELPs to induce the phase transition, and have found success in making spherical aggregates and fibers. 63,64 Although this amphiphilicity is commonly used to direct the assembly of discrete architectures, through the inclusion of carefully chosen hydrophobic domains into conjugates, 6,15,16 the conjugation of PEG to a (VPGVG) 4 peptide did not yield diblock conjugates capable of aggregation. 63 This indicates that short-ELPs, like those reported here, are perhaps not sufficiently hydrophobic, and do not exhibit amphiphilic behavior when hydrophilic domains, such as PAA, are conjugated to them.…”
Section: Resultsmentioning
confidence: 99%
“…Mackay et al [57] showed that similarly to other PAs, elastin-like PAs (ELPAs) assemble micelles with fibre-like nanostructures and possess inverse phase-transition behaviour. They synthesized elastin-like peptide amphiphiles composed from short ELPs (n = 3), which do not undergo phase transition.…”
Section: Self-assembly Of Elps Fibrillar Structuresmentioning
confidence: 99%